Immune system-related plasma extracellular vesicles in healthy aging - Zhang, Xin; Ma, Sisi; Huebner, Janet L.; Naz, Syeda Iffat; Alnemer, Noor; Soderblom, Erik J.; Aliferis, Constantin; Kraus, Virginia Byers (Frontiers in Immunology, 2024)
Objectives: To identify age-related plasma extracellular vehicle (EVs) phenotypes in healthy adults.Methods: EV proteomics by high-resolution mass spectrometry to evaluate EV protein stability and discover age-associated EV proteins (n=4 with 4 serial freeze-thaws each); validation by highresolution flow cytometry and EV cytokine quantification by multiplex ELISA (n=28 healthy donors, aged 18-83 years); quantification of WI-38 fibroblast cell proliferation response to co-culture with PKH67-labeled young and old plasma EVs. The EV samples from these plasma specimens were previously characterized for bilayer structure, intra-vesicle mitochondria and cytokines, and hematopoietic cell-related surface markers.Results: Compared with matched exo-EVs (EV-depleted supernatants), endo-EVs (EV-associated)